On the category of созерцание in "The Unknowable" by Semyon Frank and some of its philosophical roots - Woźniak, Monika (Hybris, 2018)
One of the most puzzling categories in The Unknowable by Semyon Frank is созерцание - a word close to German Anschauung and sometimes used as its translation. The aim of this article is to analyze the meaning of the category of созерцание in Frank’s book and to indicate some of its philosophical sources. First, I discuss the role the term Anschauung plays in the works of Kant and Goethe. The selection of these two authors allows, in my opinion, to describe both Frank's rooting in classical philosophy and the distinction of his approach. One can distinguish two different cognitive acts which are denoted by the word созерцание in Frank’s work: an immediate, non-discursive and synthetic cognition of objective being as well as the cognition of the unconditional being through experience that overcomes the subject- object relation. I argue that the importance of the synthetic and non-discursive intuitive cognition can be interpreted as Goethe's legacy in The Unknowable. Although Frank's usage of the term созерцание is rather far from Kant’s (which is evident in his neglect of the distinction receptive/spontaneous, fundamental in The Critique of Pure Reason), the problem Frank attempts to deal with, i. e. the possibility of the unconditioned cognition of being was important for the post-Kantian philosophers (Fichte among others) which makes Kant and the German Idealism a crucial context to understand it.